KEANEKARAGAMAN JENIS TUMBUHAN PENYUSUN VEGETASI DI KAWASAN HUTAN LINDUNG DESA UWEMANJE KAB.SIGI - Musdar, Musliani; Korja, I Nengah; Ningsih, Sri; Toknok, Bau (Universitas Tadulako, 2021)
Forests are one of the natural resources that have important meaning for human life. Forests with various functions and benefits have a very large influence both directly and indirectly on ecological, economic and social aspects. The purpose of this study was to determine the value of the diversity of plant species that make up the vegetation. This study uses the observation plot/plot method to see the diversity of the types of vegetation constituents in the Protected Forest Area of Uwemanje Village, Kinovaro District. The Important Value Index is used to determine the dominance of one species over another in a stand. Significant values were obtained from the sum of the Relative Density (KR), Relative Frequency (FR) and Relative Dominance (DR) for the level of stakes, piles and trees. The species diversity index was used to determine the species diversity of forest stands. Based on the results of research that has been carried out the types of plants that make up the vegetation in the protected forest area at the tree level found 16 species of trees from 14 families, at the pole level found 16 species from 16 families, at the sapling level found 10 species from 9 families, and at the seedling level found 10 types from 9 families. The level of Species Diversity (H¹) for each level is at the tree level H¹ = 3.81. Pile level H¹ = 3.35. The sapling level H¹ = 3.45 and at the seedling level H¹ = 3.54 belong to the high criteria.Kata Kunci: hutan, vegetasi, keanekaragaman jenis